Sialobiology. - Tiralongo, Joe (Bentham Science Publishers, 2013)
The importance of substitution by the sugar sialic acid and the role played by sialylated structures (eg. glycoproteins, glycolipids, glycoconjugates) in immune recognition, neural cell growth, embryogenesis and disease development including microbial pathogenesis and cancer progression, has become well-established. This ebook presents a summary of central aspects of sialobiology (i.e., the study of sialic acid and its relevance to biology).